Cone Beam Computed Tomography - Assisted Surgical Management of Root Canal Perforation - Abhishek Sinha; Anu Vashisht; Muktesh Mahajan; Srashti Sharma; Namrata Bajaj; Harshita Khandelwal (Oral Sphere Journal of Dental and Health Sciences, 2025)
Background: A common occurrence in endodontic treatment, root canal perforation (RCP) originates from the accidental connection between the periodontal space and the root canal. Among the various issues this condition can bring about are tooth loss, periapical lesions, and infection. Correct outcomes depend on proper treatment and early diagnosis. Case Presentation: Forty-year-old patient presented with mild discomfort, some dental movement, and greyish discoloration of tooth number 11. Clinical and radiographic exams found gutta-percha expelled from a root canal hole. A cone beam computed tomography (CBCT) scan was used to assess the size, position, degree of the hole, and concomitant periapical illness. Bone grafting and simultaneously apical sealing were used in the surgical intervention using Mineral Trioxide Aggregate (MTA) for obturation. Six months later follow-up showed significant with growth of new bone. CBCT imaging is necessary for RCP's correct diagnosis and surgical planning, to ensure accurate intervention. MTA sealed the hole tightly, also accelerating healing and preventing further infection. This case demonstrates how well-advanced imaging mixed with biocompatible materials performs to have favorable outcomes in challenging endodontic treatments. Conclusion: MTA obturation and CBCT imaging are therefore valuable tools in the management of root canal perforations, improving diagnostic accuracy, treatment precision, and long-term healing, and so patient outcomes.